Exploring Barriers to Co-Parenting After Divorce: An In-Depth Thematic Analysis Case Study - Rabiee , Zahra; Yousefi, Zahra; Bahramipourisfahani , Mansoureh (Mental Health and Lifestyle Journal, 2026)
Post-divorce parenting is a complex process that exerts profound effects on children’s psychological well-being and adjustment. Despite the importance of this period, the challenges and perspectives of parents navigating post-divorce parenting require deeper understanding in order to develop effective co-parenting conflict-resolution protocols. The present study was conducted to achieve a deeper understanding of the experiences of parents engaged in parenting after divorce. This qualitative study examined post-divorce co-parenting challenges and conflicts using inductive thematic analysis based on the approach of Braun and Clarke (2006). The study population consisted of all parents experiencing co-parenting conflicts following divorce. Participants included 13 divorced parents selected according to the principle of data saturation. Data were collected through semi-structured interviews and analyzed using the six-phase thematic analysis procedure proposed by Clarke and Braun (2006). The findings identified five major themes related to barriers to co-parenting: conflicts arising from improper redefinition of parenting roles after divorce, conflicts caused by parental neglect and misdirected parenting focus, lack of trust in the other parent’s parenting competence, reciprocal revenge-seeking behaviors, and instrumental use of the child within the parenting relationship. The findings of this study provide valuable implications for achieving deeper understanding and identifying patterns associated with co-parenting conflicts, offering practical insights for researchers and counselors working in the field of co-parenting.